2024
DOI: 10.1371/journal.pone.0299743
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of long-term COVID-19 on workers in healthcare settings? A rapid systematic review of current evidence

Moira Cruickshank,
Miriam Brazzelli,
Paul Manson
et al.

Abstract: Background Long COVID is a devastating, long-term, debilitating illness which disproportionately affects healthcare workers, due to the nature of their work. There is currently limited evidence specific to healthcare workers about the experience of living with Long COVID, or its prevalence, pattern of recovery or impact on healthcare. Objective Our objective was to assess the effects of Long COVID among healthcare workers and its impact on health status, working lives, personal circumstances, and use of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…Among the SARS-CoV-2 infection patients, all of whom were infected for the first time, the incidence of long COVID-related fatigue or brain fog was 4.27%. It was comparatively lower than that observed in the majority of other studies on long COVID among both the general population and healthcare workers [ 13 , 36 ]. The disparities were likely attributed to our inclusion of only two symptoms.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Among the SARS-CoV-2 infection patients, all of whom were infected for the first time, the incidence of long COVID-related fatigue or brain fog was 4.27%. It was comparatively lower than that observed in the majority of other studies on long COVID among both the general population and healthcare workers [ 13 , 36 ]. The disparities were likely attributed to our inclusion of only two symptoms.…”
Section: Discussioncontrasting
confidence: 68%
“…However, some studies found no links between occupational factors and SARS-CoV-2 infection in this population [ 11 , 12 ]. Regarding long COVID, the incidence also varied widely depending on the methodologies employed [ 13 ]. A case-control study of Brazilian healthcare workers showed that 27.4% developed long COVID after infection.…”
Section: Introductionmentioning
confidence: 99%